Model Isotherm Adsorpsi Triptamin menggunakan Adsorben Silika termodifikasi BSA - Deram, Rosalia Febriana; Anarato, Antonius Umbu; Lestarani, Dewi; Neolaka, Yantus A.B.; Lawa, Yosep; Kalla, Eka B.S.; Baunsele, Anselmus B.; Nitti, Fidelis; Naat, Johnson N. (Jurnal Beta Kimia, 2024)
This article reports the adsorption isotherm model of tryptamine using bovine serum albumin-modified silica adsorbent (SiO₂@BSA) obtained from Takari natural sand as a silica source. Silica was extracted from natural sand and then modified with BSA. The SiO₂@BSA adsorbent was used to adsorb tryptamine in a batch system with 5, 10, 20, 30, 40, and 50 mg/L concentrations. Tryptamine content was analyzed using a UV-Vis spectrophotometer at 423 nm. Eight models were employed to describe the adsorption isotherm of tryptamine. The modeling results revealed that tryptamine adsorption follows the Langmuir isotherm model, with an R² value of 0.938 and a maximum adsorption capacity of 7.961 mg/g. This study confirms the potential of SiO₂@BSA as an effective adsorbent for tryptamine adsorption, contributing to the development of adsorption technology for organic compounds.